2020
DOI: 10.1177/0961203320962848
|View full text |Cite
|
Sign up to set email alerts
|

Early damage as measured by SLICC/ACR damage index is a predictor of hospitalization in systemic lupus erythematosus (SLE)

Abstract: Background Hospital admissions and re-admissions in lupus patients are common occurrences that can lead to poor prognosis. Objectives We evaluated the leading causes of all-cause hospitalizations and their predictive factors in the Malaysian multi-ethnic SLE patients. Methods This is a retrospective study involving 300 SLE patients. Demographic data and details of hospitalizations from the year 1988 until 2019 were reviewed. Baseline and latest disease activity (SLEDAI-2 K) and SLICC/ACR damage index (SDI) sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…[22][23][24][25][26] The presence of any permanent damage measured by the SDI in non-pregnant patients has been shown to predict new damage accrual and complications like hospitalizations, disease activity, organ failure, and even death. 21,[27][28][29][30][31][32] Although part of these events is infrequent during pregnancy, such as mortality, some of the other mentioned complications related to damage accrual for non-pregnant SLE patients were also identified in this pregnant population, which corroborates the findings of the study.…”
Section: Discussionsupporting
confidence: 88%
“…[22][23][24][25][26] The presence of any permanent damage measured by the SDI in non-pregnant patients has been shown to predict new damage accrual and complications like hospitalizations, disease activity, organ failure, and even death. 21,[27][28][29][30][31][32] Although part of these events is infrequent during pregnancy, such as mortality, some of the other mentioned complications related to damage accrual for non-pregnant SLE patients were also identified in this pregnant population, which corroborates the findings of the study.…”
Section: Discussionsupporting
confidence: 88%
“…In other research, early damage was found to be a predictor of SLE patients' hospitalizations and more likely to occur in patients with a chronic active disease pattern. 32,33 Our findings, in addition to these data, enable us to better detect patients with imminent danger of developing damage and a need for prompt treatment.…”
Section: Discussionmentioning
confidence: 71%
“…18 A recent study reported a high early damage score (high baseline SDI) as a predictor of hospitalization. 19 In another study, it was observed that the mean SDI was higher in SLE patients who needed hospitalization. 20 Similarly, we found less damage in patients hospitalized due to active disease compared to those hospitalized due to damage ( p = .033).…”
Section: Discussionmentioning
confidence: 94%